Perhitungan Tenaga Keperawatan - Danurjaya, Danurjaya; Solehudin, Solehudin (JIMAD : Jurnal Ilmiah Multidisiplin, 2024)
Having sufficient nursing staff, services can be provided with high quality standards, optimizing patient care outcomes. The aim of this research is to provide a deeper understanding of the calculation of nursing personnel and the importance of this role in improving the quality and accessibility of health services. This research uses correlation analytics with a cross sectional approach. The population and sample in this study were 33 patient care units in a private hospital in Bogor. The instrument used in this research is the energy calculation formula The Ilyas Method. Statistical analysis uses the Independent Sample T Test. The research results showed that there was a correlation between the number of calculations needed for nursing staff and the current availability in a health service system. Nursing shortages can have serious consequences for patient satisfaction, increase the risk of medical errors, and slow response to emergencies. Holistic and coordinated strategies, such as active recruitment, talent retention, education and training, use of technology, and work schedule flexibility, need to be implemented to overcome the challenge of nursing shortages.